Verification, validation and testing in software engineering - Dasso, Aristides, 1943-; Funes, Ana, 1964- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
Validation and verification is an area of software engineering that has been around since the early stages of program development, especially one of its more known areas: testing. Testing, the dynamic side of validation and verification (V&V), has been complemented with other, more formal techniques of software engineering, and so the static verification--traditional in formal methods--has been joined by model checking and other techniques. This book offers thorough coverage of many valuable formal and semiformal techniques of V&V. It explores, depicts, and provides examples of different applications in V&V that produce many areas of software development--including real-time applications--where V&V techniques are required.